Pengaruh Model Argument Driven Inquiry terhadap Kemampuan Berpikir Tingkat Tinggi Berdasarkan Perbedaan Gaya Belajar Siswa SMP pada Materi Sistem Ekskresi - Nurfitri Hidayanti; Aa Juhanda; Gina Nuranti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This study aims to determine the effect of the Argument Driven Inquiry learning model on higher-order thinking skills based on the learning style of VIII grade junior high school students on the excretory system material. This type of research uses a quasi-experimental design, with a non-equivalent control group design. The samples of this study were students of class VIII F as the experimental class, and class VIII D as the control class at SMP Negeri 6 Sukabumi City. The instrument used is in the form of high-level thinking ability test questions or questionnaires in the form of multiple choice questions as many as 27 questions. The second instrument is using a student response questionnaire to learning using the Argument Driven Inquiry model which consists of 10 questions, and the third instrument is a student learning style questionnaire consisting of 33 statements. Based on the results of the average post-test scores in the experimental class and control class obtained 82.29 and 67.48. Based on the results of the independent sample t-test of the Argument Driven Inquiry learning model, the value of Sig. 0.000, then there is a significant effect of the Argument Driven Inquiry learning model on the students' higher-order thinking skills in junior high school.